KEPUTUSAN PEMBELIAN POCARI SWEAT ISOTONIK DIPENGARUHI OLEH KESADARAN MEREK SERTA PERSEPSI KUALITAS - Reza Anggapratama; Dwi Irnawati; Amelia Ivoka Junea; Sofie Shalzabilla Meta Firanka (Value : Jurnal Manajemen dan Akuntansi, 2023)
Through shifts in individual ways more and more activities require common sense. The growing public attention to health then influences customer consumption behavior. This research aims to see that purchasing decisions for isotonic Pocari sweat are influenced by brand awareness and perceived quality. The research method is Multiple Linear Regression. This research is expected to show that brand awareness and perceived quality influence purchasing decisions for isotonic Pocari Sweat. Bojonegoro University students who drank Pocari Sweat as samples. Non-probability sampling was used for research. A questionnaire containing 12 statements was distributed to 100 respondents to collect information. Multiple linear regression for research methods. This research shows that brand awareness variables and overall quality perceptions influence purchasing decisions where the F count is 9.942 > F table 3.09. The results also show that brand awareness affects buying decisions where the t-count is 2.664 > t-table 1.984. Meanwhile, the perceived quality variable does not influence purchasing choices; the t-count is 0.124, smaller than the t-table of 1.984. The coefficient of determination from the definition test (adjusted R2) shows that brand awareness and quality perception factors can understand 15.3% of the variation in purchasing decision factors. For comparison, various elements outside this research understand the excess of 84.7%.. Keywords: Brand, Isotonic, Pocari Sweat